Cardiac biomarkers as indicators of right ventricular dysfunction and recovery in chronic thromboembolic pulmonary hypertension patients after balloon pulmonary angioplasty therapy – a cardiac magnetic resonance imaging cohort study. (1st December 2021) - Kriechbaum, Steffen D.; Vietheer, Julia M.; Wiedenroth, Christoph B.; Rudolph, Felix; Barde, Marta; Wolter, Jan‐Sebastian; Haas, Moritz; Fischer‐Rasokat, Ulrich; Weferling, Maren; Rolf, Andreas; Hamm, Christian W.; Mayer, Eckhard; et al.
Abstract : Background: In chronic thromboembolic pulmonary hypertension, right heart failure determines outcome. Balloon pulmonary angioplasty therapy allows right heart recovery, which can be monitored by cardiac magnetic resonance imaging. This study evaluates whether cardiac biomarkers (NT‐proBNP, MR‐proANP, sST2, and PAPP‐A) are associated with cardiac magnetic resonance imaging findings prior to and after balloon pulmonary angioplasty therapy. Methods: This observational cohort study enrolled 22 chronic thromboembolic pulmonary hypertension patients who underwent balloon pulmonary angioplasty therapy and completed a six‐month follow‐up including cardiac magnetic resonance imaging. Biomarker levels were compared with findings for right heart morphology and function derived from cardiac magnetic resonance imaging. Results: Pulmonary hemodynamics improved after balloon pulmonary angioplasty therapy [pulmonary vascular resistance: 7.7 (6.0–9.0) vs. 4.7 (3.5–5.5) wood units, p < 0.001; mean pulmonary artery pressure 41 (38–47) vs. 32 (28–37) mmHg, p < 0.001]. Cardiac magnetic resonance imaging findings indicated right heart maladaptation at baseline and recovery after therapy [right ventricular end‐diastolic volume 192 (141–229) ml vs. 143 (128–172) ml, p = 0.002; right ventricular end‐systolic volume 131 (73–157) ml vs. 77 (61–99) ml (p < 0.001); right ventricular ejection fraction (RVEF) 34 (28–41) % vs. 52 (41–54) %; p < 0.001]. Biomarker level cut‐offs [NT‐proBNP 347 ng/L (area under the curve (AUC) 0.91), MR‐proANP 230 pg/L (AUC 0.78), PAPP‐A 14.5 mU/L (AUC 0.81), and sST2 48.0 ng/ml (AUC 0.88)] indicated a RVEF ≤ 35% at baseline. The dynamics of NT‐proBNP (rs = −0.79; p < 0.001), MR‐proANP (rs = –0.80; p < 0.001), and sST2 (rs = –0.49; p = 0.02) correlated inversely with the improvement in RVEF after therapy. A relative decrease of NT‐proBNP < 53% (AUC 0.86) and MR‐proANP < 24% (AUC 0.82) indicated a limited RVEF response. Conclusions: In chronic thromboembolic pulmonary hypertension patients, cardiac magnetic resonance imaging findings illustrate right heart failure and recovery after balloon pulmonary angioplasty therapy. Cardiac biomarker levels correlate with right heart parameters at baseline and their dynamics after therapy.